Pengaruh Shopping Lifestyle dan Diskon Terhadap Impulse Buying di E-commerce Shopee Pada Mahasiswa UPN “Veteran” Jawa Timur - Putri Agustin Dwi Ningrum; Hery Pudjoprastyono (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
Shopee is one of the most popular online marketplaces for consumers to purchase. The increase in online shopping during the COVID-19 pandemic can be attributed to impulse purchases driven by various factors, including more convenient shopping and discounts. This study uses a quantitative methodology and uses the variables "Shopping Lifestyle" (X1), "Discounts" (X2), and "Impulse Buying" (Y) as research variables. This study used a convenience sample of 70 people who were taken non-probabilistically. Information was collected by sending questionnaires to prospective respondents. Structural Equation Modeling (SEM) is a component-based data analysis technique that utilizes the Partial Least Squares (PLS) analysis tool. The research findings indicate that lifestyle shopping and discounts have a statistically significant positive effect on impulse purchases made on Shopee.